Over 90 endangered fish and invertebrates are caught in industrial fisheries - Leslie A. Roberson (Nature Portfolio, 2020)
Due to legislative shortfalls, species of global conservation concern can still be captured in commercial fisheries. Here the authors show that 91 threatened species are reported in catch/landing databases, 13 of which are traded internationally despite their conservation concern.